Answer:
c. 15in
Step-by-step explanation:
Answer: 2.52
Step-by-step explanation: Good luck!
Answer:
![g(x) = 2x^2 - 3x - 1](https://tex.z-dn.net/?f=g%28x%29%20%3D%202x%5E2%20-%203x%20-%201)
Step-by-step explanation:
Given
![f(x) = 2x^2 + 3x - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%5E2%20%2B%203x%20-%201)
Required
Determine g(x), if f(x) is reflected across the y axis
<em>When a function (x,y) is reflected across the y axis, the new function becomes (−x,y).</em>
<em />
In other words,
![g(x) = f(-x)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20f%28-x%29)
Calculating f(-x)
![f(-x) = 2(-x)^2 + 3(-x) - 1](https://tex.z-dn.net/?f=f%28-x%29%20%3D%202%28-x%29%5E2%20%2B%203%28-x%29%20-%201)
![f(-x) = 2x^2 - 3x - 1](https://tex.z-dn.net/?f=f%28-x%29%20%3D%202x%5E2%20-%203x%20-%201)
Substitute g(x) for f(-x)
![g(x) = 2x^2 - 3x - 1](https://tex.z-dn.net/?f=g%28x%29%20%3D%202x%5E2%20-%203x%20-%201)
<em>Hence;</em>
![g(x) = 2x^2 - 3x - 1](https://tex.z-dn.net/?f=g%28x%29%20%3D%202x%5E2%20-%203x%20-%201)
Answer:
2*5*7
Step-by-step explanation:
2*5=10
10*7=70
It Is Currently Neutral because if you're 35 ft. Underground and you raise 35 feet it 0 you're ground level